Regional Labour Market Disparities in an Enlarged European Union - Peter Huber (Austrian Institute of Economic Research (WIFO), 2008)
We characterise regional labour market problems in the EU 27 using disaggregate data on regional employment, unemployment and participation rates, by gender and 10-year age groups at the NUTS-2 level. We ask whether accession changed disparities in regional labour market conditions and to what degree the structure of employment, unemployment and participation rates in the 12 new member countries differs from the EU 15. We find that aggregate labour market disparities are comparable between the two country groups but that there are important structural differences. Performing a basic components analysis we find that five principal components (four of which are associated with the structure of employment and participations rates) explain around 90 percent of the variance in the data. Cluster analysis suggests that new member country regions are most similar in structural labour market characteristics to many German and French NUTS-2 regions. Regression analysis suggests that the correlates of aggregate regional employment and unemployment rates between the two groups do not differ dramatically but that there may be some differences with respect to employment rates of individual demographic groups.
Keywords: 330; Regional labour market disparities; Regionaler Arbeitsmarkt; Räumliche Verteilung; EU-Staaten